2014
DOI: 10.1074/jbc.m114.548693
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Assays for Superoxide and Hydrogen Peroxide

Abstract: Background: NADPH oxidases (Nox) are involved in pathogenesis of inflammatory and fibrotic diseases. Results: High-throughput screening methodology is developed for discovery and determination of Nox inhibitors and mechanism. Conclusion: Rapid and specific monitoring of superoxide and hydrogen peroxide is possible, enabling high-throughput screening of Nox isoform-specific inhibitors. Significance: The proposed strategy will enable more rigorous research on the chemical biology of Nox enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 54 publications
1
66
0
Order By: Relevance
“…Furthermore, the cell death profile induced by DOX in this setting is consistent with increased apoptosis leading to secondary necrosis, whilst the concentrations of DOX used in this study (0.5–5 μM) are relevant to plasma levels found clinically up to 1 h post‐treatment (0.1–10 μM) (Anderson et al, 1999). In a pharmacological approach, the observed effects of the pan‐NADPH oxidase inhibitor, VAS2870, on DOX (5 μM)‐induced cell death add weight to the involvement of Nox2 signalling in this model, although it should be noted that VAS2870 can exert Nox2‐independent actions (Gatto et al, 2013) and is cytotoxic at high concentrations (Zielonka et al, 2014), which we observed at 100 μM. However, at a concentration of 50 μM, which maintained cell viability, VAS2870 was shown to reduce both cytotoxicity and caspase 3/7 activity.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the cell death profile induced by DOX in this setting is consistent with increased apoptosis leading to secondary necrosis, whilst the concentrations of DOX used in this study (0.5–5 μM) are relevant to plasma levels found clinically up to 1 h post‐treatment (0.1–10 μM) (Anderson et al, 1999). In a pharmacological approach, the observed effects of the pan‐NADPH oxidase inhibitor, VAS2870, on DOX (5 μM)‐induced cell death add weight to the involvement of Nox2 signalling in this model, although it should be noted that VAS2870 can exert Nox2‐independent actions (Gatto et al, 2013) and is cytotoxic at high concentrations (Zielonka et al, 2014), which we observed at 100 μM. However, at a concentration of 50 μM, which maintained cell viability, VAS2870 was shown to reduce both cytotoxicity and caspase 3/7 activity.…”
Section: Discussionmentioning
confidence: 93%
“…A DEPMPO spin trap was used to detect O 2 •− produced by NADPH oxidase in intact HL60 cells differentiated into neutrophil-like cells ( d HL60) and stimulated with PMA (Fig. 7) (79). The EPR signal was inhibited by SOD but not by catalase, indicating that superoxide was responsible for the adduct formed, consistent with the spectral features observed, which are characteristic of a superoxide spin adduct.…”
Section: Epr Spin Trapping Of Superoxide Radical Anionmentioning
confidence: 99%
“…Thus, by profiling the products formed, in addition to the use of specific inhibitors and scavengers, the identity of the oxidant(s) can be determined (98100). In specific instances, where the involvement of other oxidants can be excluded, boronate-based probes can be used to selectively monitor the activity of NADPH oxidases (24, 79, 91, 101). Several boronate-based fluorogenic probes have been applied to monitor the activity of NADPH oxidases, including coumarin boronic acid (CBA), which upon reaction with H 2 O 2 undergoes oxidation to 7-hydroxycoumarin (COH, also known as umbelliferone) (79, 102, 103).…”
Section: Boronate-based Assays For H2o2mentioning
confidence: 99%
See 2 more Smart Citations